Informação contábil em linguagem XBRL : estudos de casos em prefeituras paranaenses - Silva, Thaís Alves da (2016)
The adoption of new technologies such as XBRL language, requires internal modifications in organizations which often reflect environmental factors. This research was a multiple case study incorporated in three City Halls in the State of Paraná, engendered in the positivist paradigm, was aimed to analyze the influence of contingency factors on the adoption of XBRL for transmitting information through SICONFI by the public administrative authority from cities in the State of Paraná. The cases were selected based on the municipal budget size to promote contrasting conditions in the studied phenomenon. The propositions and the theoretical model of the research was based in variables extracted from the Contingency Approach, covering: the Environment as an independent variable; Size, Tasks, Strategy and Structure as intervening variables; and the Technology as dependent variable. By semi structured interviews content analysis conducted with people in charge of strategical areas of the organizations and semantic differential scales collected by questionnaires directed to other servers; also from triangulating the data obtained; and the analysis of the adequacy of the empirical standard of the cases to the prognosis standard of the study has made it possible to meet the two main phases of the research: the first phase (inductive and descriptive) which has shown that the Environment represents an external contingency factor, influencing internal contingency variables directly Size, Tasks and Strategy. Such internal variables, as a reflective effect of the Environment, affect the dimensions of Centralization, Formalization, Stratification and the Complexity of the Structure. Thus, it can be inferred that the Environment indirectly influences the Structure. However, there is direct influence of the Structure on the adoption of the XBRL in the cases studied (Technology) through to the dimension of Complexity, which, together with identified latent factors: Knowledge in XBRL , Investment Potential, Computerization, Legal Expectations, Data Processing and Intentions of the Management, features an Endogenous Perspective of influence. While by Exogenous Perspective the study findings show that the variable Environment directly affects the Technology through Technological, Qualitative, of Implementation and of Supervision Conditions. For the second phase of the study (deductive and causal) the types of relationships of influence (positive and negative) of the Environment on the Size, Tasks and Technology were identified; and also the influence of the Size and Tasks on the Structure. However, it was not possible to assume the relations of influence of the Environment on the Strategy, neither of the Strategy on the Structure. It was also defined the relations of influence of the type of the Structure on the Technology regarding the adoption of XBRL: Case I (small organization) shows more features on the organismic model compared to the other and it was what showed greater willingness to voluntarily adopt XBRL; Case II (medium organization) presents a structure model at an intermediate level between the studied cases, however, it still approaches the mechanical structure, and therefore preferably not to adopt the XBRL; Case III (large organization) has the most features aimed to mechanistic model and has showed the least willingness to voluntarily adopt XBRL in SICONFI. Therefore, these findings indicate a theoretical replication of the results. However, other factors not covered by the Contingency Approach were identified which also affect the adoption of XBRL